The future of transportation energy use in the Philippines. - Hanson, Mark E. (Philippine Engineering Journal)
As the Philippines attains some progress in its program to reduce oil consumption and imports, the use of petroleum in the transportation industry will become an increasingly important factor to consider. A set of microcomputer based spread sheet simulation models were used to estimate the impact of future economic trends and conservation actions. The simulation results indicated that an economic recovery and subsequent moderate growth would also lead to increased demand for petroleum. On the other hand, economic stagnation combined with some conservation, would hold petroleum use fairly constant. Specific conservation actions, such as efficiency standards, would significantly reduce the increase in petroleum use that would occur with the resumption of economic expansion.